(3fcJ GdgejGf aj fcJ GdYejGfs - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj , UdGM GdOjf,J (B764 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg CKfGA GdebOeI GdJGSYI ef GdebOeGJ GdJi JSHb GdJQGLe (B( (3SCdJ heG GdeSFhd CYde HGdPi CQOJ hGdCeJg Ydjc HQhR (B) s
(3BNQgG (B:s
(3jfJgi HYO JQLeI jhfS Hf ejSQI (B( (3gPG BNQ eG hLOJg ef cJGH fcJ GdgejGf hgh BNQ eG dNUg hGfJNHg hGNJUQg hde jNd GSe hGMO hddg GdMeO hGdefI (B) s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B315 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B114 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B352s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B678s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdJGQjNs